Laparoscopic Evaluation of Chronic Pelvic Pain in Women - Chhetri, S; Khanna, S; Poonam, A; Sen, B (Journal of Nepal Health Research Council, 2009)
Background: Chronic pelvic pain is a common and significant disorder of women. Often the etiology of chronic pelvic pain is not clear. Methods: A descriptive hospital based study was done which included 55 women with chronic pelvic pain of more than six months duration. Ultrasonography and diagnostic laparoscopy were performed in all patients. These patients also had a psychological assessment with the SRQ (Self Reporting Questionnaire). The various causes of pelvic pain were assessed. Result: The mean age of women presenting with chronic pelvic pain was 37.1 ± 2.3 years. Ultrasonography detected abnormality in only 21 (38.2%) patients. The most common pathology detected was ovarian cysts in seven patients. Diagnostic laparoscopy was able to detect pathology in 45 (81.8%) patients. Pelvic adhesions was the most common cause of chronic pelvic pain which was present in 16 (29%) of the women, followed by PID (pelvic inflammatory disease) in seven (12.7%), endometriosis in five (9.1%), pelvic congestion in four (7.2%), pelvic tuberculosis in four (7.2%), fibroid uterus in four (7.2%), ovarian cysts in four (7.2%) and parafimbrial cyst in one patient. No abnormality on laparoscopy was detected in 10 (18.2%) patients. When evaluated for associated psychological illness it was detected in 24 (43.6%) patients. Results: Chronic pelvic pain is a common problem and presents a major challenge to health care providers because of its unclear etiology, complex natural history, and poor response to therapy. Diagnostic laparoscopy is thus an important tool in the evaluation of women with chronic pelvic pain. Key words: chronic pelvic pain, laparoscopy, ultrasonography. DOI: 10.3126/jnhrc.v7i1.2279 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 45-48